Higher Doses of FSH Used for Superovulation Do Not Adversely Affect Embryonic Ploidy: A Randomised Controlled Trial (Stimulation Resulting in Embryonic Aneuploidy Using Menopur (STREAM) Trial) - Akshara SHYAMSUNDER; Tristan HARDY; Anusch YAZDANI; Alex POLYAKOV; Robert NORMAN; Roger HART; Franca AGRESTA; Luk ROMBAUTS; Clare BOOTHROYD; Michael CHAPMAN; Prudence SWEETEN; Eleanor SOMERVILLE; et al. (Fertility & Reproduction, 2022)
Background: High dose gonadotropin stimulation protocols may increase costs, patient discomfort, likelihood of ovarian hyper stimulation syndrome (OHSS), ovarian torsion and increased bleeding after multiple ovarian punctures. In addition, it is possible that high dose stimulation may result in impaired oocyte “quality” with adverse effect of embryonic ploidy. This may negate any benefits seen from a higher oocyte yield after high dose stimulation. Aim: To determine the proportion of euploid blastocysts resulting from higher versus lower dose ovarian stimulation protocols. Method: Multicentre randomised controlled trial recruiting 57 women who were treated with ovarian stimulation using either 150 or 300 IU Menopur per day. In Vitro Fertilisation (IVF) or Intracytoplasmic Sperm Injection (ICSI) were performed according to individual unit protocol and embryos were cultured to blastocyst stage. A trophectoderm biopsy was performed for preimplant action genetic testing for aneuploidy. Results: The number of oocytes obtained from women randomised to 150 IU Menopur was between 3–17 (mean=9), whereas the number of oocytes obtained from women randomised to 300 IU Menopur was between 3–24 (mean=11). There was a positive linear relationship between serum AMH concentration and oocyte yield in both the 150 & 300 IU Menopur groups (R=0.3359, R2=0.1129 & R=0.3741, R2=0.1399). 63% of blastocysts were euploid in the 150 IU Menopur group and 75% in the 300 IU Menopur group (p=0.17). Conclusion: The higher dose ovarian stimulation protocol did not significantly increase the number of oocytes retrieved, nor did the higher dose protocol reduce the proportion of euploid embryos created. This study does not support the hypothesis that use of higher doses of gonadotropin for ovarian stimulation results in a reduction in the proportion of euploid embryos obtained after IVF.